2008
DOI: 10.1002/qua.21949
|View full text |Cite
|
Sign up to set email alerts
|

Accurate solutions for the spiked oscillators

Abstract: ABSTRACT:The one-dimensional harmonic oscillator potential plus a term of the form /x ␣ is known as the spiked oscillator potential; it constitutes a very interesting system because of its difficulties to accept perturbative and variational solutions for certain regimes of the ␣ parameter. By the use of a numerical method, we obtain accurate energy eigenvalues and eigenfunctions for a wide range of values and a few ␣ values. The accuracy of the present results is by much higher than previously published result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 42 publications
(83 reference statements)
0
3
0
Order By: Relevance
“…Afterward, the wave functions as well as the eigenvalues are calculated in a sequence by increasing the value of this parameter r 0 until the desired accuracy is achieved. Mathematically, it has been demonstrated that this procedure converges to the exact results of the original system where the spatial confinement is absent (see [41][42][43]). Hence, the artificial spatial confinement gives highly accurate results with respect to the exact values, which can not be guaranteed by other methods [41].…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…Afterward, the wave functions as well as the eigenvalues are calculated in a sequence by increasing the value of this parameter r 0 until the desired accuracy is achieved. Mathematically, it has been demonstrated that this procedure converges to the exact results of the original system where the spatial confinement is absent (see [41][42][43]). Hence, the artificial spatial confinement gives highly accurate results with respect to the exact values, which can not be guaranteed by other methods [41].…”
Section: Introductionmentioning
confidence: 88%
“…Hence, the artificial spatial confinement gives highly accurate results with respect to the exact values, which can not be guaranteed by other methods [41]. Some examples to illustrate this point are the free hydrogen atom, an electron in the Yukawa potential, the Hulthen potential, and the singular oscillator (see [41][42][43]).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation